2016
DOI: 10.4038/jas.v11i1.8079
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Growth and Yield Associated Flowering Time Variation in Sri Lankan Rice “Hondarawala”

Abstract: Breeding new varieties adaptable for changing climate is an essential need in sustainable rice production. Around 2000 Sri Lankan rice accessions at Plant Genetic Resources Centre (PGRC), Sri Lanka have not been fully characterized for the yield potential and sensitivity to mild photoperiodic differences for days to flowering (DF). DF is a candidate key determinant in yield components in rice and understanding the physiological and molecular nature for DF is important to manipulate crop yield through breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…There were positive correlations between DF and quantitative morphological characters of PH, LL and CD and a negative correlation between PW (Table 3). Similar observations were reported for Sulai variety where positive correlations were present between DF and vegetative growth characteristics (PH, CN, LN, LL and LW) (Rathnathunga and Geekiyanage, 2015). In a photoperiod experiment with Sulai, Kohu mawee and Deveraddili, the yield was reduced under LD conditions where flowering was delayed in contrast to SD conditions (Geekiyanage et al, 2012).…”
Section: Relationship Between Days To Flowering On Vegetative Growth supporting
confidence: 73%
See 1 more Smart Citation
“…There were positive correlations between DF and quantitative morphological characters of PH, LL and CD and a negative correlation between PW (Table 3). Similar observations were reported for Sulai variety where positive correlations were present between DF and vegetative growth characteristics (PH, CN, LN, LL and LW) (Rathnathunga and Geekiyanage, 2015). In a photoperiod experiment with Sulai, Kohu mawee and Deveraddili, the yield was reduced under LD conditions where flowering was delayed in contrast to SD conditions (Geekiyanage et al, 2012).…”
Section: Relationship Between Days To Flowering On Vegetative Growth supporting
confidence: 73%
“…Days to flowering (DF) among 29 Sudu wee accessions varied from 62 -106 days except for accession 4193 which did not flower during the experimental period (Table 1). Flowering time range in Sudu wee was comparatively narrow in contrast to 56 to 200+ days among 16 accessions of Hondarawala variety and 57 -179 days among 12 accessions of Sulai variety Geekiyanage, 2015 andRathnathunga et al, 2016a). Flowering time variations during late short day season towards day neutral to long day season could be due to the presence of date fixed forms explained by Chandrarathna (1964).…”
Section: Flowering Time and Morphological Variation Among Accessions mentioning
confidence: 92%
“…Delayed flowering time increased the vegetative growth and reduced the grain size (Table 5). Similar observations were reported for Sulai, Sudu wee and Hondarawala varieties, where there were positive relationships between DF and vegetative growth characteristics, while negative relationships existed between DF and yield components (Rathnathunga et al 2013;Rathnathunga et al 2015;Rathnathunga et al 2016b;Rathnathunga et al 2016c). In contrast, relationship between DF and yield components of photoperiod responsive 43 Ma wee accessions of Sri Lankan traditional rice was positive under inductive short day season (Pushpakumari et al 2017).…”
Section: Variation Among Accessions Of Sri Lankan Traditional Rice Vasupporting
confidence: 59%
“…Comparatively similar PCs were identified in studies of Sulai, Sudu wee and Hondarawala varieties, which suggested the fact that same character standards applied in all genetic diversity studies of Sir Lankan rice (Rathnathunga et al 2015;Rathnathunga et al 2016b;Rathnathunga et al 2016c) (Table 2). Pachchaperumal accessions of 8827, 3408, 3752, 5548, 5550, 5547 and 9047 of cluster one, 5546, 3946, 6834 and 5549 of cluster two, accession of 5383 of cluster three were grouped into…”
Section: Genetic Diversity Of Pachchaperumal and Suduru Samba Accessimentioning
confidence: 60%
See 1 more Smart Citation